Three‐dimensional lithospheric electrical structure of Southern Granulite Terrain, India and its tectonic implications. Issue 1 (13th January 2014) - Patro, Prasanta K.; Sarma, S. V. S.; Naganjaneyulu, K.
Abstract [1] The crustal as well as the upper mantle lithospheric electrical structure of the Southern Granulite Terrain (SGT) is evaluated, using the magnetotelluric (MT) data from two parallel traverses: one is an 500 km long N‐S trending traverse across SGT and another a 200 km long traverse. Data space Occam 3‐D inversion was used to invert the MT data. The electrical characterization of lithospheric structure in SGT shows basically a highly resistive (several thousands of Ohm meters) upper crustal layer overlying a moderately resistive (a few hundred Ohm meters) lower crustal layer which in turn is underlain by the upper mantle lithosphere whose resistivity shows significant changes along the traverse. The highly resistive upper crustal layer is interspersed with four major conductive features with three of them cutting across the crustal column, bringing out a well‐defined crustal block structure in SGT with individual highly resistive blocks showing correspondence to the geologically demarcated Salem, Madurai, and Trivandrum blocks. The 3‐D model also brought out a well‐defined major crustal conductor located in the northern half of the Madurai block. The electrical characteristics of this south dipping conductor and its close spatial correlation with two of the major structural elements, viz., Karur‐Oddanchatram‐Kodaikanal Shear Zone and Karur‐Kamban‐Painavu‐Trichur Shear Zone, suggest that this conductive feature is closely linked to the subduction‐collision tectonic processes in the SGT, and it is inferred that the Archean Dharwar craton/neoproterozoic SGT terrain boundary lies south of the Palghat‐Cauvery shear zone. The results also showed that the Achankovil shear zone is characterized by a well‐defined north dipping conductive feature. The resistive block adjoining this conductor on the southern side, representing the Trivandrum block, is shown to be downthrown along this north dipping crustal conductor relative to the Madurai block, suggesting a northward movement of Trivandrum block colliding against the Madurai block. The lithospheric upper mantle electrical structure of the SGT up to a depth of 100 km may be broadly divided into two distinctly different segments, viz., northern and southern segments. The northern lithospheric segment, over a major part, is characterized by a thick resistive upper mantle, while the southern one is characterized by a dominantly conductive medium suggesting a relatively thinned lithosphere in the southern segment.